2009
DOI: 10.1002/bem.20472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electromagnetic field on the proliferation and differentiation potential of human bone marrow mesenchymal stem cells

Abstract: Pulsed electromagnetic fields (PEMFs) have been used clinically to slow down osteoporosis and accelerate the healing of bone fractures for many years. The aim of this study is to investigate the effect of PEMFs on the proliferation and differentiation potential of human bone marrow mesenchymal stem cells (BMMSC). PEMF stimulus was administered to BMMSCs for 8 h per day during culture period. The PEMF applied consisted of 4.5 ms bursts repeating at 15 Hz, and each burst contained 20 pulses. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 46 publications
2
114
0
Order By: Relevance
“…For instance, in vitro exposure to pulsed electromagnetic fields (PEMF) at extremely low frequencies (ELF) of 15 Hz or 50 Hz, has been shown to significantly increase cell proliferation by 20% to 60% over controls, in human [48] and rat BMSC [49]. Also, 50 Hz sine wave fields of 0.5 to 1 mT have been reported to promote proliferation of rodent BMSC [29,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in vitro exposure to pulsed electromagnetic fields (PEMF) at extremely low frequencies (ELF) of 15 Hz or 50 Hz, has been shown to significantly increase cell proliferation by 20% to 60% over controls, in human [48] and rat BMSC [49]. Also, 50 Hz sine wave fields of 0.5 to 1 mT have been reported to promote proliferation of rodent BMSC [29,50].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that a 50 Hz, 0.5 mT field induces proliferation in mouse BMSC by increasing the proportion of cells entering phases S and G2 of the cycle [29]. Also, human BMSC exhibit a proliferative response to in vitro treatment with 15 Hz PEMF through increased proportions of cells undergoing phase G2/M during exposure, and of cells in phase G0/G1 at the end of the stimulation interval [48]. Recently, Li et al [49] have reported that exposure to 50 Hz, 10 mT PEMF increases proliferation in rat BMSC and blocks cell cycle in phase G1, what is interpreted by the authors as a potential cytodifferentiating effect of the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported slight enhancement in cellular proliferation but were unable to determine any significant changes in adipogenic cellular differentiation as determined by Oil Red O. 32 The use of IDEs in combination with human adiposederived stem cells provides a facile technique to culture and expose cells to regimented electric field treatments. The injection of charge into our system can be achieved by utilizing either a voltage or current source between the contact pads of the IDEs.…”
Section: Mccullen Et Almentioning
confidence: 98%
“…For example, osteogenic differentiation of hMSCs was investigated in the presence of an electric field. The results showed that alkaline phosphatase (ALP) expression was enhanced under the electric field compared to the control group and calcium mineralization was also higher in the stimulated group (Sun et al, 2009). In another example, hMSCs were exposed to an electric field during osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, external electric fields have been applied on cells cultured in tissue culture polystyrene flasks and well plates via electrodes and coins (Sun et al, 2009;Jansen et al, 2010;McCullen et al, 2010). The aim of those studies was to investigate the effect of electric fields on osteogenic differentiation of cells rather than to suggest a functional system for bone fracture healing.…”
Section: Introductionmentioning
confidence: 99%